Mozambique Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank (World Bank, Washington, DC, 2016)
This report provides an assessment of the strengths and weaknesses of the existing financial reporting infrastructure that underpins financial accounting and auditing practices in Mozambique. The assessment focuses on six pillars of financial reporting infrastructure: statutory framework, professional education and training, accountancy profession, accounting standards, auditing standards, and monitoring and enforcement of the applicable standards. The main purpose of this assessment is to assist the development and implementation of a country action plan for strengthening institutional capacity with attendant effect on enhancing corporate financial reporting in Mozambique. All the corporate entities in Mozambique, including investments with foreign participation, are affected by a serious shortage of qualified accountants and trained accounting technicians. Best estimates are that there are less than 50 fully qualified accountants working in Mozambique (mostly in the Maputo area), and that of these only 2 are citizens of Mozambique. Most of the corporate financial statements in the country are therefore prepared by accounting technicians whose level of skill and training is variable. At one extreme, a limited number of accounting technicians have completed training, which has not prepared them nearly at the level of a qualified accountant; and at another extreme, many technicians have no formal training. Most of the financial statement audits in the country are primarily carried out by representatives of the 6 international networks. The lack of senior-level local staff within those networks is of concern particularly as regulators lack any capacity to monitor the quality of financial reporting.